2017
DOI: 10.1080/03601234.2016.1273003
|View full text |Cite
|
Sign up to set email alerts
|

Fast extraction of polychlorinated dibenzo-p-dioxin and polychlorinated dibenzofuran in sewage sludge and soil samples

Abstract: The current environmental legislations recommend monitoring chemical contaminants such as polychlorinated dibenzo-p-dioxins and polychlorinated dibenzofurans before the use of sewage sludge on the agricultural land. In this study, a solid-liquid extraction with low-temperature purification (SLE-LTP) was optimized and validated to determine 2,3,7,8-tetrachlorodibenzo-p-dioxin and 2,3,7,8-tetrachlorodibenzofuran in sewage sludge and soil samples. The analyses were performed by gas chromatography-mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Therefore, acetonitrile was chosen as the appropriate phase for extracting these compounds in water. Similar results were reported by Andrade et al 20 and Silvério et al 22 using the same extraction phase.…”
Section: Lle-ltpsupporting
confidence: 90%
See 3 more Smart Citations
“…Therefore, acetonitrile was chosen as the appropriate phase for extracting these compounds in water. Similar results were reported by Andrade et al 20 and Silvério et al 22 using the same extraction phase.…”
Section: Lle-ltpsupporting
confidence: 90%
“…23,24 The presence of PCDD/Fs in real samples depends on several factors such as matrix type, analyte concentration, sample collection period and extraction and detection methodologies used; therefore, most of the literature studies did not quantify PCDD/Fs in real samples. 1,17,18,20,25,26…”
Section: Real Samplesmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, previous works have shown that solid-liquid extraction coupled with low-temperature purification (SLE-LTP) has met these characteristics when applied to other environmental contaminants. 15,16 One of the main advantages of this methodology is the extraction and cleaning in a single step.…”
Section: Introductionmentioning
confidence: 99%